The Importance of the Default Mode Network in Creativity—A Structural MRI Study. (12th December 2013) - Kühn, Simone; Ritter, Simone M.; Müller, Barbara C. N.; van, Rick B.; Brass, Marcel; Dijksterhuis, Ap
Abstract Anecdotal reports as well as behavioral studies have suggested that creative performance benefits from unconscious processes. So far, however, little is known about how creative ideas arise from the brain. In the current study, we aimed to investigate the neural correlates of creativity by means of structural MRI research. Given that unconscious and less controlled processes are important in creative thinking, structural brain research may find a positive correlation between well‐established creativity measures and cortical thickness in brain structures of the default mode network (i.e., the counterpart of the cognitive control network). Individuals performed the Alternative Uses task by which an individual's cognitive flexibility and the average uniqueness and average creativity of a participant's ideas were assessed. We computed optimized voxel‐based‐morphometry (VBM) to explore the correlation between inter‐individual differences in creativity and inter‐individual differences in gray matter volume. For all creativity measures, a positive correlation was found between creative performance and gray matter volume of the default mode network. These findings support the idea that the default mode network is important in creativity, and provide neurostructural support for the idea that unconscious forms of information processing are important in creativity. Theoretical and practical implications are discussed.